Assessing the Importance of Key Terms in UN SDGs Through Citizens Labs - Kouzaridi, Emily; Partaourides, Harris; Tsapatsoulis, Nicolas; Djouvas, Constantinos (My University, 2023)
This study employs a novel methodology to assess the importance of key terms in the United Nations (UN) Sustainable Development Goals (SDGs) by incorporating citizens' perspectives through keyword evaluation in citizens' labs. Representative keywords, sourced from reliable references like the Cyprus University of Technology SDG Keyword Mapping (CUT), are initially selected to represent the key concepts and objectives of each SDG. Citizens assess these keywords during a lab session, utilizing an interactive platform like Mentimeter. The participants dynamically provide their input by choosing the most significant SDG keywords according to their opinions consequently assigning importance weights to them. This approach fosters a more comprehensive understanding of the SDGs and aligns sustainable development initiatives with citizen priorities.